2002
DOI: 10.1007/bf00766645
|View full text |Cite
|
Sign up to set email alerts
|

Condensation reactions of phenolic resins III: self-condensations of 2,4-dihydroxymethylphenol and 2,4,6-trihydroxymethylphenol (1)

Abstract: This study reexamined the kinetics of the condensation reactions of hydroxymethylphenols with the purpose of elucidating the reaction mechanisms. This report discusses experimental results on the self-condensations of 2,4-dihydroxymethylphenols (2,4-DHMP) and 2,4,6trihydroxymethylphenol (THMP), focusing on the order of reaction. The relations between the initial rates of reaction and the initial concentrations of reactants were investigated. Results quite different from those of previous reports were obtained.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…The inflection point at the concentration of 1.2 mol/L agreed with that shown in Figure 2. Moreover, the inflection at this concentration is similar to the phenomenon obtained from the kinetic experiment of Kamo et al, 9 indicating the change in the molecular interaction. Higher values of E a reflect a strong dependence of T 1 on the temperature, indicating that the hydroxymethyl group is easy to rotate.…”
Section: Dependence Of T 1 On the Temperaturesupporting
confidence: 79%
See 2 more Smart Citations
“…The inflection point at the concentration of 1.2 mol/L agreed with that shown in Figure 2. Moreover, the inflection at this concentration is similar to the phenomenon obtained from the kinetic experiment of Kamo et al, 9 indicating the change in the molecular interaction. Higher values of E a reflect a strong dependence of T 1 on the temperature, indicating that the hydroxymethyl group is easy to rotate.…”
Section: Dependence Of T 1 On the Temperaturesupporting
confidence: 79%
“…Considering these results together with previous kinetic works, 9,10 we assume a reaction pathway for the self-condensation of THMP (Fig. 5).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The kinetics and mechanisms of the individual reactions in the PF system are apparently the key issues and also the foundation for understanding the chemistry of PF. However, by surveying the literature from the middle of the last century to recent years, discrepant results for the kinetics and mechanisms of the base-catalyzed condensation reactions between hydroxymethylphenols (HMPs) have been reported [9,10,11,12,13,14,15,16,17,18,19]. In some earlier studies, the condensations of HMPs were reported to be first-order [9,10,11], pseudo-first-order or second-order [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, Higuchi et al confirmed that the self-condensation of 2-hydroxymethylphenol (2-HMP) is kinetically of genuine first-order and the QM hypothesis seems to hold in such a reaction [ 15 ]. However, in their continuous studies on 4-hydroxymethylphenol (4-HMP) [ 16 ], 2,4-dihydroxymethylphenol (2,4-DHMP) [ 17 ] and 2,4,6-trihydroxymethylphenol (2,4,6-THMP) [ 18 ], the condensations appeared to be of fractional order, ranging from 1.1~2.0. Further, the reaction order varied with the change of the NaOH/HMP molar ratio and with the change of the HMP concentration.…”
Section: Introductionmentioning
confidence: 99%